Functional outcome of proximal 1/3rd, distal 1/3rd and diaphysial tibial fractures in adults operated with expert tibial nailing - Kiran, Uduthala Sai; S., Surendra Babu; Nitin, Kurakula; Desai, Tarun; Y. S., Kaushik; Krishnan, Rinju (International Journal of Research in Orthopaedics, 2021)
Background: Fractures of the tibial shaft are increasing due to high velocity trauma and industrialisation. Not only they are common but also difficult to treat. Until recently surgeons had to rely on non-operative treatment, V nailing, plates and screws and external fixator but they had their drawbacks like prolonged immobilisation infection, delayed union and non-union. Numerous modifications in nail and screw design have led to development of the expert tibial nail. Multidirectional interlocking screws ensure that alignment can be well maintained and stability preserved in short proximal or distal tibial segments. Methods: 30 patients were admitted and operated during September 2014 to September 2016 in Mamata general hospital Khammam. All patients were evaluated with Klemm Borner’s criteria and complications following surgery. Results: 87% of patients achieved good or excellent results, fair results were obtained in 3 (10%) patient and poor result in one (3%) patient. 2 (6%) patients had malunion, 2 (6%) patients had delayed union, 1 (3%) patient had deep infection led to implant failure. Conclusions: Intramedullary nailing is a safe and effective technique for the treatment of tibial metaphyseal fractures. It avoids the additional soft-tissue dissection associated with traditional open procedures as well as the complications associated with external fixators. Expert tibial nail can give excellent functional and clinical results. Complications such as failure of the bone-implant construct or post-operative malallignment are avoidable if careful pre-operative planning is allied with meticulous surgical technique.